Integrating Technology in Education: Disney+ Hotstar as a Tool for Vocabulary Improvement - Agustiani, Aulia; Rery, Nurul Masyithah; Putri, Hikmah Zalifah (Universitas Pahlawan Tuanku Tambusai, 2025)
Enhancing vocabulary acquisition requires teachers to be innovative in the recent advancement of technology, particularly in the instructional process. Teachers can use many platforms to benefit from emerging technology in education. One of them is using Disney+ Hotstar that promotes its subtitled content. This paper explored the impacts of using Disney+ Hotstar on students' vocabulary mastery—the present study distributed a questionnaire to 35 sixth-semester students of one university in Riau. As a result of the research, it was discovered that Disney+ Hotstar could enhance students' vocabulary mastery. It allowed the students to discover new vocabularies while watching TV shows or movies on Disney+ Hotstar. For future studies, it is highly recommended that English teachers adopt Disney+ Hotstar content as an innovative teaching strategy for enhancing students' vocabulary mastery. In addition, it can be authentic, up-to-date, contextual and interesting learning material for students to gain more knowledge and enhance their vocabulary mastery. In summary, emerging technology in education can enhance students’ knowledge and understanding. There are so many platforms and digital tools that teachers can use in teaching and learning processes to create interesting and engaging teaching and learning activities.